SERHIY ANDRIYOVYCH SMORSHCHOK (TO THE 90TH ANNIVERSARY SINCE BIRTHDAY) - Voloshyn, V.D.; Stechenko, L.O.; Voloshyn, O.S.; Smorshchok, Yu.S. (World of Medicine and Biology, 2020)
The article is devoted to the life, scientific and pedagogical activity of Professor Serhiy Andriyovych Smorshchok – famous histologist, laureate of the State Prize of the USSR (1982), head of the Department of Histology and Embryology (1977–1995) of Ternopil State Medical Institute, organizer and longtime head of the electron microscopy laboratory, Academician of Ukrainian Ecological Academy of Sciences (1993). The article highlights biographical data, analyzes the scientific achievements of the scientist, his contribution to the development of modern histology, combustiology, medical education. S.A. Smorshchok made the major impact to the study of the pathogenesis of burns, compensatory–adaptive processes in tissues and organs at severe thermal burns and the search for ways to correct destructive changes. Serhiy Andriyovych's professional scientific, pedagogical and organizational activities, personal qualities contributed to the development of the Ukrainian histological school, its worthy representation at the international level.
Keywords: histology; electron microscopy; burn disease; compensatory–adaptive processes; antioxidants; enterosorbents; xenografts